2016
DOI: 10.1080/09712119.2016.1268965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth curves using non-linear regression function in Japanese quail

Abstract: This study was conducted to determine the goodness of fit of Gompertz, Logistic, Von Bertalanffy, Richards, Levakovich and Janoschek growth models in Japanese quail. Therefore, weekly live-weight data obtained from 372 females and 339 males were fitted. Females' live weights were found to be higher than that of males, and the first divergence in the growth of female and male birds occurred in 21-28 days, and it survived until the experiment (P < .001). The coefficient of determination (R 2), adjusted coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 20 publications
(28 reference statements)
9
38
1
Order By: Relevance
“…The estimated values of 1.03 for m parameter in Richards model in male data ( Table 5) indicated that Richards model had close performance to Logistic model. The Richards model was also reported to be superior to other models for body mass in several studies in birds [35,36]. The same values of AIC and BIC were obtained for Weibull, Bridges and Janoscheck models in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…The estimated values of 1.03 for m parameter in Richards model in male data ( Table 5) indicated that Richards model had close performance to Logistic model. The Richards model was also reported to be superior to other models for body mass in several studies in birds [35,36]. The same values of AIC and BIC were obtained for Weibull, Bridges and Janoscheck models in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, they concluded that selection did not change the shape of the growth curve in females. Kaplan and Gürcan (2018) reported similar conclusions for the selection impact on the shape of the growth curve in Japanese quail.…”
Section: Growth Curve Parameters (Fixed)supporting
confidence: 61%
“…On the other hand, Beiki et al (2013) found that the Richards model was better than other models in fitting growth data of Japanese quail in both sexes. Kaplan and Gürcan (2018) suggested the Gompertz model as the second best, after the Richards model, for fitting growth data of Japanese quail.…”
Section: Goodness Of Fitmentioning
confidence: 99%
“…Animal growth is a complex physiological and morphological process from hatching to maturity. It is defined as the increase in BW and organ size per unit of time or age ( Yang et al., 2006 , Kaplan and Gürcan, 2018 ). Animal growth has been summarized using mathematical equations or growth curves that result in mathematical parameters that are biologically interpretable ( Tzeng and Becker, 1981 , Aggrey, 2002 , Yang et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%